If it's not what You are looking for type in the equation solver your own equation and let us solve it.
20(1.3x-0.4)-3x=0.6(5x-10)
We move all terms to the left:
20(1.3x-0.4)-3x-(0.6(5x-10))=0
We add all the numbers together, and all the variables
-3x+20(1.3x-0.4)-(0.6(5x-10))=0
We multiply parentheses
-3x+20x-(0.6(5x-10))-8=0
We calculate terms in parentheses: -(0.6(5x-10)), so:We add all the numbers together, and all the variables
0.6(5x-10)
We multiply parentheses
3x-6
Back to the equation:
-(3x-6)
17x-(3x-6)-8=0
We get rid of parentheses
17x-3x+6-8=0
We add all the numbers together, and all the variables
14x-2=0
We move all terms containing x to the left, all other terms to the right
14x=2
x=2/14
x=1/7
| (((2x+60)+(3x+10-6)=180)*2) | | (((2x+60)+(3x+10)=180)*2 | | (((2x+60)+(3x+10)=180)*2)-7) | | (((2x+60)+(3x+10)=180)*2))+(7) | | (((2x+60)+(3x+10)=180)*2)-7 | | 5x+10=15* | | Y=9.75x+800 | | (((2x+60)+(3x+10)=180)*2) | | (((2x+60)+(3x+10)=180)*2)+7 | | 7(x-6)=-3(5+x) | | 2x+28=3x+14 | | 0.436-b=24.996(1-0) | | 3x+28=3x+14 | | 3(y-3)=5(2y+1 | | a=3+√5/2a+1/aa-1/a | | 7+x+-15=-2 | | 5=3a+2 | | -5(6+p)=40 | | 15x/11-7x=13 | | 40=(p+6) | | 2(x-)-7=16 | | x/3,5=15 | | 23.8-x=0.40 | | 2/3x=3/8+7/12 | | 9x-4x+10=7x-30 | | y2-4y-12=0 | | 30y+2=68y= | | 8x2-62x+99=0 | | 8x=5=11 | | 8x÷10=40 | | 3=13/4k-5 | | 35x+40+6x=8x-12-9x |